The Linguistic Struggle and Volunteering to Serve the Arabic Lan Eguage - Highlights on Distinguishedxperiences [In Arabic] - Boufellagua, Mohammed saif alislam (Milev Journal of Research and Studies, 2022)
This research, tagged with: “The Linguistic Struggle and Volunteering to Serve the Arabic Language - Highlights on Distinguished Experiences,” strives to monitor multiple, overlapping issues that are of great importance in our time; In the first part, it deals with a number of issues related to linguistic pride and identity in the era of globalization. As for the second part of the research; The researcher presents a set of successful experiences in the field of dictionaries, dictionaries and linguistic maintenance.